A self‐consistent κ‐model for anomalous transport due to electrostatic, interchange‐dominated E × B drift turbulence in the scrape‐off layer and implementation in SOLPS‐ITER. Issue 5 (21st March 2022) - Dekeyser, Wouter; Coosemans, Reinart; Carli, Stefano; Baelmans, Martine
Abstract: The ad‐hoc description of anomalous transport through diffusive relations with manually tuned coefficients is currently one of the main limitations in mean‐field plasma edge codes, seriously restricting their interpretive and predictive capabilities. In this paper, we attempt to improve that description by relating the anomalous transport coefficients to the turbulent kinetic energy κ as a measure for the local intensity of the turbulence. Using RANS techniques from hydrodynamic turbulence and insights from their recent successful application to 2D electrostatic E × B drift turbulence modelling for the scrape‐off layer, we propose a transport equation for κ and discuss its coupling with the mean‐field transport equations. The main features of the model include (a) an analytically exact interchange source of κ which introduces the ballooning character of the transport; (b) fast parallel transport of κ through the connection with parallel current fluctuations; and (c) consistent transport reduction due to the impact of mean E × B flow shear. The resulting model has been implemented in the new extended grids version of SOLPS‐ITER, enabling for the first time mean‐field simulations self‐consistently combining classical parallel transport with mean‐field drifts and anomalous transport with the code. A first assessment of the model has been made for a representative C‐Mod case study, highlighting the promising features of the model. Further analysis is needed to investigate in detail the impact of the different new terms in the model across operational regimes, and determine the new closures constants based on larger sets of turbulence simulations and experimental data.